Erosion of Tolerance and Religious Social Conflict in Indonesia: Case Studies of the Ambon and Tolikara Conflicts - Mayulita, Silar (Program Studi Studi Agama Agama Fakultas Ushuluddin dan Pemikiran Islam, 2025)
This article discusses two major social conflicts in Indonesia, namely the Ambon Conflict and the Tolikara Conflict, with a focus on analyzing the sources of triggers, the role of religion in the escalation of conflicts, and the efforts made to resolve them. The Ambon conflict was triggered by a clash of beliefs between Muslims and Christians, exacerbated by social stratification, ethnic differences, as well as local political provocation and third parties. Meanwhile, the Tolikara conflict began with tensions between Muslims and Christians that culminated in violence, showing the potential for religion-based horizontal conflict. This research uses a descriptive qualitative method with a literature review approach, aiming to describe in depth the characteristics and dynamics of the two conflicts. Data was collected through a literature study of relevant primary and secondary sources. The results show that both conflicts have the same roots, namely inter-religious tensions triggered by social, political and economic factors. The resolution of the conflict in Ambon involved a reconciliation approach and interfaith dialogue, while in Tolikara, despite the resolution efforts, the challenge of building interfaith trust remains a major obstacle.